Iron(II) Spin Crossover Coordination Polymers Derived From a Redox Active Equatorial Tetrathiafulvalene Schiff-Base Ligand - Qiu, Ya-Ru; Cui, Long; Ge, Jing-Yuan; Kurmoo, Mohamedally; Ma, Guijun; Su, Jian (Frontiers in Chemistry, 2021)
Two polymorphic FeII coordination polymers, [FeIIL(TPPE)0.5] (1) and [(FeII3L3(TPPE)1.5)] (2), were obtained from a redox-active tetrathiafulvalene (TTF) functionalized ligand (H2L = 2,2'-(((2-(4,5-bis-(methylthio)-1,3-dithiol-2-ylidene)benzo[d][1,3]dithiole-5,6-diyl)bis-(azanediyl))bis-(meth anylylidene))(2E,2E')-bis(3-oxobutanoate)) and a highly luminescent connector (TPPE = 1,1,2,2-tetrakis(4-(pyridine-4-yl)phenyl)-ethene). Complex 1 has a layered structure where the TPPE uses its four divergent pyridine coordination in trans positions to the flat TTF Schiff-base ligand, and complex 2 has an unprecedented catenation of layers within two interpenetrated frameworks. The redox activity of the TTF moiety was retained in these coordination polymers. Complex 1 shows gradual spin transition behavior without hysteresis. And the fluorescence intensity of TPPE in 1 changes in tandem with the spin crossover transition indicating a possible interplay between fluorescence and SCO behavior.